The unity of the Proslogion: reason and desire in the monastic theology of Anselm of Canterbury - Bayer, John (Anselm studies and texts, 2021)
"Interpretations of Anselm's Proslogion range between the extremes of 'rationalism' and 'fideism' because of the challenge of unifying its philosophical and devotional aspects. In this book, Bayer argues that a 'monastic interpretation' - or an interpretation that takes seriously the intellectual significance of our existential commitments - offers a powerful compromise. Through an extensive study of Anselm's spiritualty, especially as it is manifested in his letters and homiletic works, coupled with a profound study of Anselm's philosophy of language in the De grammatico and Monologion, Bayer aims to reveal the Anselmian unity of life and thought, and thereby also the harmony between faith and reason. In this way, he defends the Proslogion as a unified and probative argument"--